The Synthesis Science of Targeted Vapor-Phase Metal–Organic Framework Postmodification - Kim, In Soo; Ahn, Sol; Vermeulen, Nicolaas A; Webber, Thomas E; Gallington, Leighanne C; Chapman, Karena W; Penn, R. Lee; Hupp, Joseph T; Farha, Omar K; Notestein, Justin M; Martinson, Alex B. F (Journal of the American Chemical Society, 2020)
The postmodification of metal organic frameworks (MOFs) affords exceedingly high surface area materials with precisely installed chemical features, which provide new opportunities for detailed structure–function correlation in the field of catalysis. Here, we significantly expand upon the number of vapor-phase postmodification processes reported to date through screening a library of atomic layer deposition (ALD) precursors, which span metals across the periodic table and which include ligands from four distinct precursor classes. With a large library of precursors and synthesis conditions, we discern trends in the compatibility of precursor classes for well-behaved ALD in MOFs (AIM) and identify challenges and solutions to more precise postsynthetic modification.